Blowing Off Steam: Tuffisite Formation As a Regulator for Lava Dome Eruptions - Kendrick, Jackie E.; Lavallée, Yan; Varley, Nick R.; Wadsworth, Fabian B.; Lamb, Oliver D.; Vasseur, Jérémie (Frontiers in Earth Science, 2016)
Tuffisites are veins of variably sintered, pyroclastic particles that form in conduits and lava domes as a result of localized fragmentation events during gas-and-ash explosions. Those observed in-situ on the active 2012 lava dome of Volcán de Colima range from voids with intra-clasts showing little movement and interpreted to be failure-nuclei, to sub-parallel lenses of sintered granular aggregate interpreted as fragmentation horizons, through to infilled fractures with evidence of viscous remobilization. All tuffisites show evidence of sintering. Further examination of the complex fracture-and-channel patterns reveals viscous backfill by surrounding magma, suggesting that lava fragmentation was followed by stress relaxation and continued viscous deformation as the tuffisites formed. The natural tuffisites are more permeable than the host andesite, and have a wide range of porosity and permeability compared to a narrower window for the host rock, and gauging from their significant distribution across the dome, we posit that the tuffisite veins may act as important outgassing pathways. To investigate tuffisite formation we crushed and sieved andesite from the lava dome and sintered it at magmatic temperatures for different times. We then assessed the healing and sealing ability by measuring porosity and permeability, showing that sintering reduces both over time. During sintering the porosity-permeability reduction occurs due to the formation of viscous necks between adjacent grains, a process described by the neck-formation model of Frenkel (1945). This process leads the granular starting material to a porosity-permeability regime anticipated for effusive lavas, and which describes the natural host lava as well as the most impervious of natural tuffisites. This suggests that tuffisite formation at Volcán de Colima constructed a permeable network that enabled gas to bleed passively from the magma. We postulate that this progressively reduced the lava dome’s ability to seal and build pressure that drives explosions. Indeed, the time interval between explosions during 2007 to 2011 gradually increased before the onset of a period of quiescence starting in June 2011. We suggest that the permeability evolution during tuffisite formation has important consequences for modeling of gas-and-ash explosions, common at dome-forming volcanoes.